IMPROVING STUDENT LEARNING OUTCOMES THROUGH MODELS DISCOVERY LEARNING IN IPS LEARNING IN CLASS IV SDN 06 DUHIADAA POHUWATO DISTRICT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Formula problem in study This is is with Model Learning Discovery Learning can improve student learning outcomes in social studies learning at SDN 06 Duhiadaaa. The purpose of this research is to improve social studies learning outcomes through the Discovery Learning model on student class IV elementary school 06 Duhiadaa. Method study Which used is Classroom action research. Data collection techniques namely observation, tests and documentation. The subjects of this study were fourth grade students at SDN 06 Duhiadaa amount 20 person student.